Anticancer Potential of Retama monosperma (L) Boiss in the Beni Mellal Khenifra Region - Nadia, Ouzennou; Mohamed, Aboufaras; Karima, Selmaoui (Archives of Clinical and Biomedical Research, 2023)
Background: Moroccan cancer patients use traditional herbal medicine. The prevalence of the use of medicinal plants is 31% in this country. No ethnobotanical study has targeted these patients in the Beni Mellal Khénifra region, a region known for the extensive use of medicinal plants. Objective: Enumerate the plants used against cancer in the Beni Mellal- Khenifra region, to highlight the use of a botanical species, not yet described in previous studies in Morocco, and to describe its ethnobotanical characteristics, its frequency of use and its possible effects on cancer. Methods: An ethnobotanical survey was conducted at the level of the regional oncology center of Béni Mellal between June 2020 and April 2021. A structured interview with 410 cancer patients contacted according to a sampling by quotas made it possible to collect socio-demographic, clinical and ethnobotany data. Results: The prevalence of herbal medicine use was 38% (n = 156). 34 plant species used belong to 19 botanical families. Retama monosperma (L) Boiss (11%) took second place after Marrubium vulgare L. (16%), it was followed by other plants depending on the frequency: Juniperus oxycedrus L., Allium cepa L., Allium Sativum L., Nigella sativa L., Artemisia herba-alba Asso and Trigonella foenum-graecum L. Conclusion: R. monosperma is a plant that has never been included in the list of plants used by cancer patients in Morocco. Further research is needed to evaluate the pharmacological and toxicological aspects of this plant and its interest for cancer.